A didática do curso de pedagogia da Unesp/Marília (1963-2005) Uma história da formação de professores, por meio da história de constituição de uma disciplina acadêmica - Tezza, Leonardo Marques (Editora Oficina Universitária, 2020)
In search of a history of teacher training at FFC-Unesp/Marília, the author presents the trajectory of the Didactics disciplines in the Pedagogy course at FFC-Unesp/Marília between the years 1963 - 2005 strongly marked by a path that sought to align itself with the official demands on the directions in which Didactics should follow to juxtapose theory and teaching practice in order to preserve its fundamental character and, at the same time, in favor of the instrumentalization of its future teachers in an attempt to meet the needs required in the construction of this field of knowledge that had as its official discourse the urgency to articulate theory and practice to remedy the deficiencies in the training of teachers who needed training that was more consistent with the Brazilian educational reality. In this book, Leonardo Marques Tezza seeks to understand, through the data and information contained in official documents, such as in the curriculum matrices presented, the range of the various processes that constituted the disciplines of Didactics in the course and period in focus.